Recruitment/Selection and Training/Development Practices: Value-Added Contribution towards Organizational Effectiveness - Abang Ekhsan, Abang Othman (Nicolae Titulescu University of Bucharest,Romania, 2009)
The purpose of this paper is to examine the applications of key human resource management functions of recruitment/selection and training/development and explore perceptions on their value-added contribution towards organizational effectiveness in the context of two major Japanese owned multinational electronics companies in Malaysia. A mixed-methodological approach via case studies and questionnaire surveys was used for this study. Overall 29 questionnaires from the two companies were analyzed. In addition, the views of the Executive Director, Head of HR, line mangers and engineers were sought regarding their role, involvement, policies/practices and their perceptions on the value-added contributions of HR towards organizational effectiveness. Analysis of the questionnaire responses and interviews shows that there are similarities between their practices and the tenets of traditional Japanese management system (JMS) with some modifications and adaptations to meet local context. The overall findings indicate that their recruitment/selection and training/development practices are influenced by their JMS which encourages specific human capital creation through a well elaborated and integrated HRM practices linking towards organizational goals. Their systematic and effective management of HR system lead to an especially important source of competitive advantage, hence, contributing towards organizational effectiveness. Though by no mean to be conclusive, the result of this study support the notion that higher strategic HRM effectiveness correlates positively towards organizational effectiveness. This paper provides some insights and practical implications to HR practitioners and line managers into approaches to strategic HRM practices as a source of competitive advantage.